Inside the Fog: Assessing Foreign Policy Expertise in the Brazilian Federal Senate - Vinicius Santos (Dados: Revista de Ciências Sociais)
Abstract This study aims to explore the contributions of the Brazilian Senate members within the Committee on Foreign Relations and National Defense (CRE), focusing on key elements for assessing expertise. Analyzing 21,994 interventions from 2013 to 2023, obtained via the specialized R language package senatebR, we employ Natural Language Processing techniques to extract metrics across four dimensions: Lexical Complexity, Syntactic Structure, Style, and Conceptual Depth. Using principal component analysis (PCA), we develop a specialization index and conduct a K-means cluster analysis, revealing three groups: Prolix, Expert, and Concise. Some senators, referred to as “Prolix”, employ complex language with varied sentence structures, while others, labeled as “Experts”, exhibit sophisticated syntax and rich vocabulary. Additionally, a group labeled “Concise” prefers simpler language with fewer sentence variations. This research identifies distinct communication styles within the committees, shedding light on how senators convey their positions and engage in deliberations.